Intracardiac echocardiography-guided implantation of the Watchman FLX left atrial appendage closure device - Turagam, Mohit K; Neuzil, Petr; Petru, Jan; Hala, Pavel; Mraz, Tomas; Baroch, Jiri; Lekesova, Veronika; Prokopova, Milena; Dukkipati, Srinivas R; Reddy, Vivek Y (Journal of cardiovascular electrophysiology, 2021)
BACKGROUND: The next-generation Watchman FLX left atrial appendage closure (LAAC) device has: (1) an atraumatic closed distal end, (2) reduced height, (3) a recessed screw hub to decrease device-related thrombus (DRT), (4) two rows of J-shape anchors so redeployment is possible after full recapture, and (5) ability to treat a greater size range of LAA ostia. OBJECTIVE: To report, for the first time, the feasibility and safety of intracardiac echocardiography (ICE)-guided Watchman FLX implantation. METHODS: A single-center prospective registry of atrial fibrillation patients planned for LAAC with the FLX device underwent ICE-guided implantation with conscious sedation. Transesophageal echocardiography (TEE) imaging was done preprocedure (to assess LAA size and exclude thrombus) and at clinical follow-up at 6-12 weeks. Clinical outcomes were LAA closure success, complications, leak, or DRT on follow-up TEE and major safety events. RESULTS: The study included 30 patients: age 75 ± 8 years, 53% men, CHA2 DS2 -VASc 4.6 ± 1.6, and HAS-BLED 3.4 ± 1.1. The primary indication was prior bleeding in 60% (72% GI bleeding). The LAA orifice width and length were 22.7 ± 3.1 and 25.7 ± 5.7 mm, respectively. Technical success was 100% (the first-choice device was used in 28 of 30). Procedure time was less than 30 min in 27 of 30 cases, with 36 ± 15 ml contrast used. The final device size was 29.2 ± 4.7 mm with 21.6 ± 4.5% compression. There were no procedure-related complications. Follow-up TEE at a median 47 days follow-up showed 100% device success with no DRT or peridevice leak ≥5 mm. Major safety events occurred in 6.6% (2/30). CONCLUSION: The Watchman FLX device can be safely implanted with intraprocedural ICE imaging instead of TEE.
Keywords: Female; Atrial Fibrillation; Atrial Appendage; výsledek terapie; ženské pohlaví; Cardiac Catheterization; cévní mozková příhoda; lidé; Stroke; Treatment Outcome; Aged, 80 and over; Male; Aged; srdeční katetrizace; echokardiografie transezofageální; Echocardiography, Transesophageal; fibrilace síní; senioři nad 80 let; senioři; mužské pohlaví; síňové ouško; Humans